A Contextual Data Offloading Service With Privacy Support - Gomes, Francisco Anderson de Almada; Viana, Windson; Rocha, Lincoln S.; Trinta, Fernando (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Mobile devices, such as smarthphones, became a common tool in our daily routine. Mobile Applications (a.k.a. apps) are demanding access to contextual information increasingly. For instance, apps require user’s environment data as well as their profiles in order to adapt themselves (interfaces, services, content) according to this context data. Mobile apps with this behavior are known as context-aware applications (CAS). Several software infrastructures have been created to help the development of CAS. However, most of them do not store the contextual data, once mobile devices are resource constrained. They are not built taking into account the privacy of contextual data either, due the fact that apps may expose contextual data, without user consent. This paper addresses these topics by extending an existing middleware platform that help the development of mobile context-aware applications. Our extension aims at store and process the contextual data generated from several mobile devices, using the computational power of the cloud, and the definition of privacy policies, which avoid dissemination of unauthorized contextual data.